2014
DOI: 10.1111/brv.12141
|View full text |Cite
|
Sign up to set email alerts
|

Historical ecology: past, present and future

Abstract: The term 'historical ecology' has been used with various meanings since the first half of the 20th century. Studies labelled as historical ecology have been produced in at least four academic disciplines: history, ecology, geography and anthropology. Although all those involved seem to agree that historical ecology concerns the historical interconnectedness of nature and human culture, this field of study has no unified methodology, specialized institutional background and common publication forums. Knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 111 publications
1
69
0
2
Order By: Relevance
“…, Stark et al. ), but are the first to show this relationship in a historical ecological context (sensu Balée , Szabó ). Supporting that soil microbial processes under historical and existing reindeer densities could be highly similar, the enhanced P limitation in the HMGs agreed with the findings from similar vegetation transition studies with existing high reindeer densities (Stark and Väisänen , Sitters et al.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…, Stark et al. ), but are the first to show this relationship in a historical ecological context (sensu Balée , Szabó ). Supporting that soil microbial processes under historical and existing reindeer densities could be highly similar, the enhanced P limitation in the HMGs agreed with the findings from similar vegetation transition studies with existing high reindeer densities (Stark and Väisänen , Sitters et al.…”
Section: Discussionmentioning
confidence: 94%
“…Historical ecological studies have generally demonstrated a high importance of historical legacies on present‐day ecosystem structures and processes (Balée , Kardol et al. , Szabó , Valls Fox et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Historical approaches are increasingly used to better understand the structure and function of contemporary ecosystems and landscapes that have been affected by human activities for centuries or millennia (Swetnam et al 1999). The discipline that addresses this historical relationship between human beings and the biosphere at different scales is usually known as ''historical ecology'' (Szabó 2015; but see also Balée 2006). Almost all the definitions of historical ecology emphasize the interconnectedness of humans and nature in the past, as well as the fact that influences and feedback mechanisms are active in both directions (reviewed in Szabó 2015).…”
Section: Historical Ecology and Biological Invasionsmentioning
confidence: 99%
“…The discipline that addresses this historical relationship between human beings and the biosphere at different scales is usually known as ''historical ecology'' (Szabó 2015; but see also Balée 2006). Almost all the definitions of historical ecology emphasize the interconnectedness of humans and nature in the past, as well as the fact that influences and feedback mechanisms are active in both directions (reviewed in Szabó 2015). Therefore, historical ecology encompasses studies that aim either to understand more about human history with the help of nature phenomena or about nature with the help of history (Szabó 2010).…”
Section: Historical Ecology and Biological Invasionsmentioning
confidence: 99%
See 1 more Smart Citation